Beyond re-membering: Phantom sensations of congenitally absent limbs - Brugger, Peter (The National Academy of Sciences, 2000)
Phantom limbs are traditionally conceptualized as the phenomenal persistence of a body part after deafferentation. Previous clinical observations of subjects with phantoms of congenitally absent limbs are not compatible with this view, but, in the absence of experimental work, the neural basis of such “aplasic phantoms” has remained enigmatic. In this paper, we report a series of behavioral, imaging, and neurophysiological experiments with a university-educated woman born without forearms and legs, who experiences vivid phantom sensations of all four limbs. Visuokinesthetic integration of tachistoscopically presented drawings of hands and feet indicated an intact somatic representation of these body parts. Functional magnetic resonance imaging of phantom hand movements showed no activation of primary sensorimotor areas, but of premotor and parietal cortex bilaterally. Movements of the existing upper arms produced activation expanding into the hand territories deprived of afferences and efferences. Transcranial magnetic stimulation of the sensorimotor cortex consistently elicited phantom sensations in the contralateral fingers and hand. In addition, premotor and parietal stimulation evoked similar phantom sensations, albeit in the absence of motor evoked potentials in the stump. These data indicate that body parts that have never been physically developed can be represented in sensory and motor cortical areas. Both genetic and epigenetic factors, such as the habitual observation of other people moving their limbs, may contribute to the conscious experience of aplasic phantoms.